Prevalence and determinants of adverse perinatal outcomes of preeclampsia with severe features at two selected public hospitals in Addis Ababa, Ethiopia - Mesfin Tadese; Wogene Asefa Damesa; Gebeyehu Shumet Solomon; Girma Wogie Fitie; Yohannes Moges Mitiku; Saba Desta Tessema; Agizew Endale (Frontiers Media S.A., 2024)
BackgroundPreeclampsia is a new onset of hypertension and either proteinuria or end-organ failure after 20 weeks of gestation. It is a prevalent cause of perinatal mortality, morbidity, and neonatal complications in developing nations including Ethiopia. Thus, the aimed to assess the prevalence and determinants of adverse perinatal outcomes among women with preeclampsia with severity features (PEWSF) at two selected public hospitals in Addis Ababa, Ethiopia, 2023.MethodA cross-sectional study was carried out among 348 mothers between January 1, 2023, and July 1, 2023. A structured, pre-tested questionnaire was used to gather data from in-person interviews and a review of the patient's medical record. The statistical program Epi-Data version 4.6 was used to enter the data, and SPSS version 26.0 was used for analysis. Binary logistic regression analysis was used to find factors that were associated with unfavorable perinatal outcomes. A p-value of less than 0.05 was used to declare the significance level.ResultThe overall prevalence of unfavorable perinatal outcomes was 59.2% (95% CI: 54.0-63.8). Among the complications, low birth weight, prematurity, NICU admission, and a low fifth-minute APGAR score, encompass 48.9%, 39.4%, 20.4%, and 14.7%, respectively. No formal education [OR = 5.14, 95% CI: (1.93-13.63)], unemployment [OR = 0.42, 95% CI: (0.24-0.73)], referral cases [OR = 2.03, 95% CI: (1.08-4.06), inadequate antenatal care (ANC) contact [OR = 3.63, 95% CI: (1.22-10.71)], and family history of hypertension [OR = 1.99, 95% CI: (1.03-3.85)] have shown a statistically significant association with unfavorable perinatal outcomes.ConclusionIn this study, the prevalence of unfavorable perinatal outcomes was high compared to other studies in Ethiopia. Level of education, occupation, mode of admission, ANC contact, and family history of hypertension were significant predictors of unfavorable perinatal outcomes. Socio-economic development, improving referral systems, and adequate antenatal care contact are needed to improve unfavorable outcomes. Additionally, antenatal screening and specialized care for high-risk mothers, e.g., those with a family history of hypertension are recommended.